Production of biodiesel from acid oil using sulfuric acid as catalyst: Kinetics study - Marchetti, Jorge Mario (2011)
Biodiesel production is becoming more relevant due to its environmental advantages together with the global petroleum situation regarding decreases of the reserves, instability of the prices and so on. The kinetics of the esterification and transesterification reaction of an acid oil (10% of initial free fatty acid) was studied using ethanol and a homogenous acid catalyst. The controlling step method was employed to obtain the kinetic equations, and nonlinear multiparametric routine was implemented to estimate the kinetic parameters. The selected reaction rate represented the experimental data for several operating conditions satisfactorily.